2003
DOI: 10.1038/sj.ejcn.1601551
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the glycaemic index of foods: interlaboratory study

Abstract: Objective: Practical use of the glycaemic index (GI), as recommended by the FAO=WHO, requires an evaluation of the recommended method. Our purpose was to determine the magnitude and sources of variation of the GI values obtained by experienced investigators in different international centres. Design: GI values of four centrally provided foods (instant potato, rice, spaghetti and barley) and locally obtained white bread were determined in 8 -12 subjects in each of seven centres using the method recommended by F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
210
2
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(226 citation statements)
references
References 26 publications
8
210
2
6
Order By: Relevance
“…The sample size was determined based on previous studies , Wolever, 2003, with a power of 80% and Po0.05. The AUC for glucose, insulin, C-peptide and GLP-1 were calculated using the trapezoid rule (Wolever et al, 1991).…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…The sample size was determined based on previous studies , Wolever, 2003, with a power of 80% and Po0.05. The AUC for glucose, insulin, C-peptide and GLP-1 were calculated using the trapezoid rule (Wolever et al, 1991).…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…Capillary rather than venous blood sampling is preferred for reliable GI testing (Wolever et al, 2003). Duplicate 25-ml aliquots of whole blood was deproteinised in 250 ml of ice cooled perchloric acid (2.5%), centrifuged for 4 min at 2415 Â g and stored at À20 1C for blood glucose analysis.…”
Section: )mentioning
confidence: 99%
“…It has also been reported that there is quite a substantial inter-laboratory difference in GI estimates (for example, 30 GI unit difference between rice and spaghetti), showing methodological difficulties in the measurement of GI and in turn potentionally leading to erroneous food table data. [42][43][44] Our study shows that the effects of different meals on postprandial glucose metabolism can be considerably different despite a similar energy, carbohydrate, protein and fat contents of the meals and thus a conscious choice might help to control postprandial blood glucose and blood insulin.…”
Section: Discussionmentioning
confidence: 99%